Acute dengue encephalitis during pregnancy - Reyna-Villasmil, Eduardo (2023)
Dengue is a public health problem. Most patients develop clinical signs ranging frommild illness to hemorrhagic syndrome. Unusual neurological manifestations are rareand there is increasing evidence of neurotropism by the virus. Dengue encephalitisis the result of the multisystem disorder that occurs in severe infection and duringpregnancy can be difficult to diagnose. In addition, it is important to consider it asa differential diagnosis in patients in endemic areas in patients with acute febrileillness and neurological symptoms. The management of dengue encephalitis duringpregnancy is a challenge and it is necessary to perform all possible tests to decidethe optimal and accurate management to avoid maternal complications. A case ofacute dengue encephalitis during pregnancy is presented.